Effect of quarry dust on concrete performance - Noor Aini Syafiqah Binti Abd Rahim (School of Environmental Engineering, University Malaysia Perlis, 2014)
The quarry dust is a waste material at the quarry site after the stone is crushed. To reduce the waste material in this world, reuse it is one of the solutions. So that the waste product will not be as a harmful material or rubbish that can messed up world. The quarry dust will be used as partial replacement for cement proportion based on percentage.